Mitos Kopi Teman Setia Rokok dalam Perspektif Teologis Islam Nusantara: Harmonisasi yang Diperdebatkan - Muhamad Yusuf Amin Nugroho; Robingun Suyud El Syam (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The research aims to explore the myth of coffee as a loyal friend of cigarettes from the theological perspective of Indonesian Islam, using a descriptive qualitative approach and inductive analysis. The research results concluded; that theologically in Islamic Nusantara, drinking coffee and smoking are not prohibited in Islam. However, this recommendation is only for people who by drinking coffee and cigarettes will get a lot of inspiration. Through smoking and drinking coffee, the distance between the santri and the abangan (general public) can be shortened. The most important aspect of coffee and cigarette law is not the ijtihad regarding halal, haram and makruh, but the implications of the ijtihad inviting Muslims to appreciate and respect other, different cultures. Research implications: the importance of understanding theology in its essence, not just its external aspects. The study invites further, more in-depth research in more specific areas.